The influences of natural environment upon the evolution of sands dunes in tropical environment along Medinipur Coastalarea, India - Sudip Dey; Pijush Ghosh; Amitava Nayak (Indonesian Journal of Geography, 2005)
This papaer assesses development of coastal sand dunes particulary along tropical coast. in depth study along on coastal dune morphology along Medinipur coastal track shows that sea levels remained very dynamic during the Holocene period. Evidence of Holocene sea level changes are found which were responsible for for the origin almost parallel distinct dune colonies through the geological past along this coastal track. The existence of tropical-monsoon climate with its seasonal phenomena plays an important the barrier property of dunes as well. in this paper possible biologcal interactions between sand mass of dunes and vegetation in different stages of development has also been dealt.